Le dessin de design en tant qu’œuvre en soi - Airton Cattani (Appareil)
Design concept processes always require the use of drawing as a tool for representation and anticipation of the industrial production of any object. Design drawing can therefore be considered as a kind of translation of the designer’s work into a wordless language, which can supposedly be decoded universally. But, far from having a unique or innate interpretation, design drawing is subject to different levels of clarity, from the designer, the transmitter of knowledge, to the receptor/reader’s understanding, which vary according to the historical period and society in which the decoding occurs. Like text, interpretation of the design drawing has to be seen in the light of a “grammar of images” which will take into account the particularities of its time. Drawing, in its various forms, is essential in all areas of design, but its functions will apparently be exhausted at the end of the object’s production process, since its original functions will have been fulfilled. But some drawings depart from the purely operational context of industrial production. In these cases the drawing becomes understood as a work with its own value, as a work of art. There is nothing new about the characteristics of some drawings and physical architecture and design models being linked not solely to the production process but also to issues related to the market for cultural and museum objects, exhibited in museums and sold in art galleries and auction rooms, especially in countries with a long tradition of this type of cultural marketplace, such as those of North America, Europe and some Asian countries. This article will examine the characteristics of these concept drawings and the particularities of their social journey, considering that they can become objects of a specific non-textual interpretation, not just as technical objects, but also as independent and unique works in themselves, paying special attention to the different contexts in which this type of drawing can in the final analysis become an artwork with its own value.